Microstructure analysis and mechanical properties of dissimilar AA6061-AA7075 laser brazing with prefixed ER5356 filler - Haneef, M. S.; Aiman, M. H.; Muhammad Naqiuddin, Mat Salleh; Quazi, M. M.; Mahadzir, I. (IOP Publishing, 2021)
Laser brazing uses a filler metal for joining without melting the base material. This process is a versatile joining technique for a wide range of applications including automotive, aerospace, and medical field because of the ability in joining dissimilar metal and resulted good quality in surface's joint. This study consists of aluminium alloy of AA6061 and AA7075 as a base material with aluminium based ER5356 as a wire filler. Laser brazing was performed using 1.2 kW of laser power, while wire filler was let to be prefixed without using the wire feeder because of using the existing laser welding machine. Microstructure of the joints were studied using 3D measuring laser microscope OLS5000. Besides that, mechanical properties of the joints were evaluated by performing tensile test and hardness test. Microstructures of the brazed joints show the differences in the grain structure followed by the difference's hardness value on each region. The brazed joint shows the average ultimate tensile strength reached 154.71 MPa which was 50% of joint efficiency. However, there is porosities at the fracture surface of the joint.